Psychometric properties of the Brazilian version of Pfeffer's Functional Activities Questionnaire - Assis, Luciana de Oliveira; de Paula, Jonas J.; Assis, Marcella G.; de Moraes, Edgar N.; Malloy-Diniz, Leandro F. (Frontiers in Aging Neuroscience, 2014)
Pfeffer’s Functional Activities Questionnaire (FAQ) is one of the most commonly employed tools in studies on pathological cognitive ageing. Despite the different versions of the questionnaire translated for use in clinical practice, few studies have analyzed the psychometric properties of the Brazilian version of the FAQ (P-FAQ). Thus, the aim of the present study was to analyze the P-FAQ with regard to internal consistency, factorial structure and associations with demographic factors (age, sex and schooling), depressive symptoms, cognitive measures and other measures of functionality. One hundred sixty-one older adults were divided into four groups (91 with dementia, 46 with mild cognitive impairment, 11 with psychiatric disorders and 13 healthy controls). All participants were evaluated by cognitive, behavioral and functional tests and scales. Their caregivers answered the P-FAQ. The questionnaire showed high internal consistency (α = 0.91). Factor analysis revealed a two-factor structure, which, accounted for 66% of the total variance. The P-FAQ was not correlated with demographic factors, was weakly correlated with depressive symptoms (ϱ = 0.271, p < 0.01, R² = 7%) and strongly correlated with cognitive measures (Matttis Dementia Rating Scale total score: ϱ = -0.574, p < 0.01, R² = 33%) as well as complex instrumental activities of daily living (ϱ = -0.845, p < 0.01, R² = 71%). Cognitive performance and depression status were independent predictors of P-FAQ scores in regression models. The present findings indicate that the P-FAQ has satisfactory reliability, internal consistency, construct validity and ecological validity. Therefore, this questionnaire can be used in clinical practice and research involving the Brazilian population of older adults.